Chloranerectuslactone V, a New Sesquiterpene from Chloranthus erectus Verdc. - Thu Huong, Tran; Van Thong, Nguyen; Thi Minh, Tran; Huyen Tram, Le; Tuan Anh, Nguyen; Duc Cuong, Ho; Van Cuong, Pham; V. Ca, Diep (Letters in Organic Chemistry, 2014)
A new secoeudesmanolide, named chloranerectuslactone V (1), along with three known compounds, chloranthalactone B (2), 9-hydroxy-heterogorgiolide (3), and β-sitosterol (4) have been isolated from the n-hexane fraction of the methanol extract of the leaves of Chloranthus erectus. Their structures were determined by spectroscopic analysis including MS and 2D NMR.
Keywords: secoeudesmanolide